Manure and Doxycycline Affect the Bacterial Community and Its Resistome in Lettuce Rhizosphere and Bulk Soil - Blau, Khald; Jacquiod, Samuel; Sørensen, Søren J.; Su, Jian-Qiang; Zhu, Yong-Guan; Smalla, Kornelia; Jechalke, Sven (Frontiers in Microbiology, 2019)
Manure application to agricultural soil introduces antibiotic residues and increases the abundance of antibiotic resistant bacteria (ARB) carrying antibiotic resistance genes (ARGs), often located on mobile genetic elements (MGEs). The rhizosphere is regarded as hotspot of microbial activity and gene transfer, which can alter and prolong the effects of organic fertilizers containing antibiotics. However, not much is known about the influence of plants on the effects of doxycycline applied to soil via manure. In this study, the effects of manure spiked with or without doxycycline on the prokaryotic community composition as well as on the relative abundance of ARGs and MGEs in lettuce rhizosphere and bulk soil were investigated by means of a polyphasic cultivation independent approach. Samples were taken 42 days after manure application and total community DNA was extracted. Besides a pronounced manure effect, doxycycline spiking caused an additional enrichment of ARGs and MGEs. High throughput quantitative PCR revealed an increase of tetracycline, aminoglycoside, and macrolide-lincosamide-streptogramin B (MLSB) resistance genes associated with the application of manure spiked with doxycycline. This effect was unexpectedly lower in the rhizosphere than in bulk soil, suggesting a faster dissipation of the antibiotic and a more resilient prokaryotic community in the rhizosphere. Interestingly, the tetracycline resistance gene tetA(P) was highly enriched in manure-treated bulk soil and rhizosphere, with highest values observed in doxycycline-treated bulk soil, concurring with an enrichment of Clostridia. Thus, the gene tetA(P) might be a suitable marker of soil contamination by ARB, ARGs and antibiotics from manure origin. These findings illustrate that the effects of manure and doxycycline on ARGs and MGEs differ between rhizosphere and bulk soil, which needs to be considered when assessing risks for human health connected to the spread of ARG in the environment.